2014
DOI: 10.6018/reifop.17.3.204071
|View full text |Cite
|
Sign up to set email alerts
|

Los hábitos lectoescritores en los alumnos universitarios

Abstract: ResumenEsta investigación analiza y describe los hábitos lectoescritores de los estudiantes universitarios dentro y fuera de las aulas. Para ello, nos hemos apoyado en la información proporcionada por los estudiantes que ha sido recogida a través de dos cuestionarios: uno de naturaleza descriptiva aplicado a una muestra de trescientos estudiantes de dos programas de Grado de la Universidad de Sevilla; el otro, de carácter específico (con tres versiones diferentes) completado por tres submuestras elegidas en fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
4
0
5
Order By: Relevance
“…Going a step further in education, analyses have been developed with subjects in university education that have traced the reading habit that students acquire during their academic development. According to the results, university students prefer to read in their own home, rather than at the university [33,34]. In addition, we cannot ignore that these students, like those of primary and infant education, form their reading habit using information and communication technologies (ICTs).…”
Section: Family Learning and Readingmentioning
confidence: 99%
“…Going a step further in education, analyses have been developed with subjects in university education that have traced the reading habit that students acquire during their academic development. According to the results, university students prefer to read in their own home, rather than at the university [33,34]. In addition, we cannot ignore that these students, like those of primary and infant education, form their reading habit using information and communication technologies (ICTs).…”
Section: Family Learning and Readingmentioning
confidence: 99%
“…Van Hoof, Cueva Navas, Fan, Pacheco, and Cordero (2015) found similar results in an Ecuadorian sample: Students valued their reading assignments but often did not read them. In Mexico, Aguilar Pérez, Curz Covarrubias, and Aguilar Cruz (2014) surveyed students at the University of Guadalajara and concluded that students did not allocate sufficient time to reading, and Guzmán-Simón and García-Jiménez (2014) found that students had difficulty generalizing knowledge from reading materials. In Peru, Barboza-Palomino and Ventura-León (2017) found that students’ reading speed could be enhanced but not their comprehension.…”
Section: Review Of Literaturementioning
confidence: 99%
“…En España, han sido escasos los estudios sobre los hábitos lectores y escritores de los alumnos universitarios (Granado, 2014;Guzmán-Simón & García-Jiménez, 2014), su comparación entre universidades (Mateos, Villalón, De Dios, & Martín, 2007) y la perspectiva del profesorado universitario (Villalón & Mateos, 2009). Sin embargo, los datos de dichos estudios corroboran las afirmaciones de Tynjälä (1998) y Mateos y Solé (2009), quienes advierten de una alfabetización académica basada en la reproducción del discurso (repetición de conocimientos aprendidos) y en un aprendizaje superficial.…”
Section: Conclusionesunclassified
“…Björk et al, 2003;Coffin et al, 2003), en España los recientes proyectos aún no han despertado el interés de las instituciones universitarias (Solé, Teberosky, & Castelló, 2012;Corcelles, Cano, Bañales, & Vega, 2013). Bajo el influjo de las investigaciones realizadas en el Reino Unido, los estudios españoles han abordado las alfabetizaciones académicas en la universidad, donde describen una situación crítica tanto en relación a las prácticas de lectura y escritura de los alumnos (Solé, Mateos, Miras, Martín, Castells, Cuevas, & Graciá, 2005;Mateos et al, 2007;Guzmán-Simón & García-Jiménez, 2014) como la percepción de los profesores respecto a los géneros escritores que desarrollan los universitarios en las aulas . Por otro lado, la escritura de los Trabajo Fin de Grado, Trabajo Fin de Máster y las tesis doctorales muestra cómo son deficitarias las competencias de los alumnos españoles para desarrollar el proceso de planificación, textualización, revisión y reescritura de este tipo de géneros discursivos (Castelló, Corcelles, Iñesta, Bañales, & Vega, 2011;Castelló, Iñesta, Pardo, Liesa, & Martínez-Fernández, 2012;Castelló, Iñesta, & Corcelles, 2013).…”
Section: Introductionunclassified